A puncture-proof, cut-proof, comfortable and breathable composite material and preparation method thereof
By using screen printing technology to arrange resin arrays on high-deformed energy-absorbing substrates, the problem of difficult to control the uniformity of the coating layer of the anti-spun and cutting-proof material is solved, and the material is stably, cutting, waterproof, breathable and soft Comfort and performance.
Patent Information
- Application Number
- CN202110762217.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-07-06
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-07-06
AI Technical Summary
In the prior art, the uniformity of the coating layer of the anti-spun and cutting-proof material is difficult to control, resulting in unstable stabilization and unsolidation of waterproof and breathable properties and soft and comfortable properties.
Using screen printing and curing technology, the particle-enhanced resin is arranged regularly on the base cloth with high deformation energy absorption. The resin array is arranged in a regular manner and has a gap to form a soft, breathable, lightweight composite with anti-spun and anti-cutting effect. Material.
It achieves both stab resistance, cutting resistance, waterproof, breathable and soft and comfortable performance, and improves the wear resistance and service life of the material.
Smart Images

Figure CN115572456B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a puncture-proof, cut-proof, comfortable and breathable composite material and a preparation method thereof, belonging to the field of functional composite materials. Background Art
[0002] In recent years, ordinary police uniforms are far from meeting the safety protection requirements of police security personnel. There have been many cases where on-duty personnel have missed opportunities to act due to the lack of effective sharp injury protection equipment, and even lost their lives.
[0003] The development of puncture protection materials has gone through three stages so far, and the corresponding products are hard, semi-rigid and soft puncture protection materials. Early hard and semi-rigid protective materials were mainly made of metal materials or metal and fiber fabric composites. These materials have excellent protective properties, but they generally have disadvantages such as being bulky, inflexible to wear, and not breathable, which seriously limits their promotion and commercial application value. In the 21st century, soft protective materials made of high-performance fibers such as UHMWPE, Kevlar and their composite materials have become the main force in this field; compared with traditional hard and semi-rigid protective materials, the biggest advantage of soft protective materials is that they are light and comfortable to wear.
[0004] Currently, researchers have chosen to use a three-dimensional fabric integrated molding method to increase the puncture protection performance, which can greatly improve the mechanical transmission and air permeability between the protective layers. However, the fiber material itself has limited tolerance to punctures, and the number of layers and tissue density required are still very large. On the one hand, the increase in the number of layers makes it difficult to weave, and on the other hand, the increase in density makes it difficult to improve the flexibility of movement. The researchers also used post-finishing methods to enhance the fabric, while ensuring the protective performance, while retaining the softness and lightness of the fabric as much as possible. The American company Criminology coated the knitted fabric with resin to improve the stab and cut protection performance; Jessie B et al. impregnated the thermoplastic film into the aramid fabric by hot pressing to obtain the composite material, which greatly improved the stab and cut resistance performance; Patent CN105696357A evenly coated the mixed resin on both sides of the aramid woven fabric, and overlapped several layers up and down, and prepared the stab and cut resistance material by molding drying and curing treatment; Li Guobiao mixed the liquid resin and ceramic particles in a certain mass ratio to obtain a mixed liquid, and evenly coated the mixed liquid on the non-metallic bulletproof substrate to prepare the non-metallic stab and cut resistance material; Ma Feifei et al. proposed that by fixing a layer of adhesive on the surface of the high-performance fabric, and then using a sandblasting machine to evenly spray rigid particles on it, after the composite fabric is stacked in multiple layers, it has good stab and ballistic resistance. Although the hardness and stab resistance of the protective material can be improved by surface coating enhancement, the uniformity of the coating layer is difficult to control, which easily leads to the unstable stab and cut resistance of the protective material, and the surface coating is easy to peel off after multiple washings or friction, resulting in the attenuation of the protective performance, which greatly shortens the service life of the protective material. Summary of the invention
[0005] Based on the above-mentioned defects of the prior art, the purpose of the present invention is to provide a composite material that is stab-proof, cut-proof, comfortable and breathable, and a preparation method thereof. In order to solve the problems in the prior art that the uniformity of the resin coating layer is difficult to control, the stab-proof and cut-proof performance is unstable, and the waterproof, breathable, soft and comfortable performance cannot be taken into account. The present invention conforms to the development trend of soft sharp weapon injury protection materials. From the perspective of breaking through the common key technologies of soft protective materials, it proposes a unique design concept of "combining rigidity and flexibility". The screen printing curing technology is used to regularly arrange the particle-reinforced resin on a base cloth that can be highly deformed and energy-absorbing. The resin array is arranged regularly and leaves a certain distance between each other to form a soft, breathable, lightweight composite material with stab-proof and cut-proof effects; the present invention is of great significance in reducing the number of casualties caused by sharp weapons in violent conflicts, ensuring personal safety, and reducing economic losses.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A composite material that is puncture-proof, cut-proof, comfortable and breathable, characterized in that the composite material comprises a hard protective array formed by a high-energy-absorbing base fabric and a circular or polygonal resin preform, and the high-energy-absorbing base fabric is treated with water and oil resistance.
[0008] Preferably, the high-energy absorption base cloth is made of high-performance fibers, the high-performance fibers are filaments or staple yarns, the high-performance fibers are preferably one or more of aramid, high-strength and high-modulus polyethylene, and high-strength polyester, the fineness of the high-performance fibers is 5.5tex-80tex, and more preferably, the fabric structure of the high-energy absorption base cloth is plain or twill, preferably 2 / 1 twill; the warp density of the high-energy absorption base cloth is 50-1000 strands / 10cm, and the weft density is 50-1000 strands / 10cm.
[0009] Preferably, the base fabric is surface treated with a waterproof and oil-proof treatment agent, and the waterproof and oil-proof treatment agent is a hexafluorocarbon waterproof and oil-proof agent or a fluorine-free waterproof and oil-proof agent; the ratio of the waterproof and oil-proof treatment agent to deionized water is 20-80:100; the treatment method is: the base fabric is immersed in the spray treatment agent for 5-20s, then taken out, dried at 80-120℃, and then shaped and baked at 160℃-180℃ for 30-120s.
[0010] Preferably, the composite material has a cut resistance of A7-A9 according to ANSI / ISEA 105-2016 standard, a puncture resistance of EN388-2016 standard level 3 or above, a waterproof performance of GB / T 4745-2012 level 4 or above, and a wear resistance of EN388-2016 level 3 or above.
[0011] Preferably, the polygonal hard protection array is preferably a regular hexagon, a fan, a regular pentagon, or a triangle; the side length or diameter of the circular or polygonal hard protection array is 0.5-5 mm, each array is evenly arranged, and the distance between adjacent arrays is 0.05-1.5 mm.
[0012] On the other hand, the present invention also provides a method for preparing the above-mentioned stab-proof, cut-proof and comfortable breathable composite material.
[0013] It includes the following steps:
[0014] S1. Preparation of high energy absorption base fabric and surface waterproof and oil-proof treatment;
[0015] S2, preparing a resin preform;
[0016] S3. The resin preform is compounded on a high energy absorption base fabric by screen printing to form a hard protective array, thereby obtaining a composite material.
[0017] Preferably, in step S3, the screen printing method is specifically as follows: placing the mold above the high-energy-absorbing base cloth treated in step S2, pouring a resin preform into the mold, using a scraper to apply a certain pressure to the resin preform and moving it at a uniform speed, so that the resin preform is squeezed from the mesh part of the mold to the base cloth by the scraper, and then performing a curing treatment process, the curing temperature is 100-130°C, and the curing time is 30-60min.
[0018] Preferably, in step S2, the method for preparing the resin preform is:
[0019] S21, surface treatment of inorganic powder;
[0020] S22, preparation of curing agent solution: add latent curing agent powder and accelerator into a container, then add N,N-dimethylformamide, place the container containing the three mixtures in a 52-60°C water bath and stir continuously until the powder is dissolved and the solution is clear, thereby obtaining a curing agent solution;
[0021] S23, wetting and dispersing inorganic powder: adding an antioxidant and an anti-settling dispersant to the curing agent solution, and adding the surface-treated inorganic powder, and stirring evenly to wet and disperse the inorganic powder;
[0022] S24, preparing a mixture of inorganic powder and resin: mechanically stirring the inorganic powder and the thermosetting resin after being wetted and dispersed, mixing them evenly, and vacuuming to remove excess bubbles to obtain a mixture;
[0023] S25, preparing a resin preform; the mixture is allowed to stand at room temperature for 24-48 hours or at 70-90° C. for 30-60 minutes for pre-curing, and then slowly stirred again to obtain a resin preform.
[0024] Preferably, in step S21, the inorganic powder surface treatment method is specifically:
[0025] S211, preparing a silane coupling agent treatment agent: preparing a silane coupling agent and deionized water in a ratio of 1:15-25 to obtain a silane coupling agent treatment agent for standby use; the silane coupling agent is preferably one of KH550, KH560 and KH570;
[0026] S212, surface treatment: weigh appropriate amounts of silicon dioxide, titanium dioxide, aluminum oxide, wollastonite and barium sulfate, stir them evenly, add a sufficient amount of the silane coupling agent treatment agent and stir to ensure full contact, the treatment time is 45-120 seconds;
[0027] S213, drying: the inorganic powder treated in step S312 is placed in an oven for drying at a temperature of 80-120° C. for a drying time of 30-80 min.
[0028] Preferably, the weight proportions of the above raw materials are: 10-15 parts of silicon dioxide, 16-20 parts of aluminum oxide, 8-12 parts of wollastonite, 1-5 parts of barium sulfate, 0.5-3 parts of titanium dioxide; 40-60 parts of the thermosetting resin, 7-15 parts of NN-dimethylformamide, 3-6 parts of latent curing agent, 0.1-1.5 parts of accelerator; 5-15 parts of anti-settling dispersant, 0.05-0.2 parts of antioxidant, and 0.1-1.0 parts of silane coupling agent.
[0029] The beneficial technical effects obtained by the present invention are:
[0030] (1) The present invention performs waterproof and oil-proof treatment on the high energy absorption base fabric to prevent the flow, diffusion and penetration of the resin preform. If the waterproof and oil-proof treatment is not performed, when the resin preform is subsequently composited on the high energy absorption base fabric by screen printing to form a hard protective array, the resin preforms will be connected into one piece and cannot form a hard protective array. In addition, the rapid flow, diffusion and penetration of the resin preform will make the fabric hard, affecting the final performance of the fabric.
[0031] (2) The polygonal hard protective array contains a large amount of high-hardness inorganic powder. The hard protective array has high hardness and good wear resistance, and can meet the requirements of high cutting resistance and high wear resistance. There is a certain gap between the protective arrays to meet the bending deformation, thereby maintaining the overall softness. The hard protective array itself has a water-repellent effect, and the bottom high-energy-absorbing base fabric is treated with waterproof and oil-proof treatment, so that the prepared composite fabric has a waterproof effect.
[0032] (3) The resin preform has high fluidity during the molding process. In the optimized scheme of the preparation method of the present invention, pre-curing is first performed to improve the viscosity of the resin so as to maintain the shape of the resin particles. In addition, if the density of the inorganic powder is large or uneven, it is easy to cause precipitation and cannot be evenly dispersed. The pre-curing process can effectively solve the above problems and facilitate the uniform dispersion of the inorganic powder in the resin. In the present invention, the waterproof treatment of the bottom base fabric is preferably carried out by spraying, and a large number of gaps are present on the surface. Together with the gaps between the resin arrays, the breathability requirements of the composite material can be well met. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a display diagram of a composite material product prepared by a method for preparing a composite material that is puncture-resistant, cut-resistant, comfortable and breathable according to an embodiment of the present invention;
[0034] Figure 2 This is a display diagram of a composite material product prepared by a method for preparing a composite material that is puncture-resistant, cut-resistant, comfortable and breathable in another embodiment of the present invention; DETAILED DESCRIPTION
[0035] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the preferred embodiments of the present application, rather than all the embodiments. These specific features, structures or characteristics in the embodiments can be combined in one or more embodiments in any suitable manner. Therefore, it should be clear to those skilled in the art that various changes and modifications can be made to the embodiments described herein without departing from the scope and spirit of the present application. In addition, for the sake of clarity and brevity, the description of known functions and structures is omitted in the embodiments.
[0036] The term "and / or" in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, B exists alone, and A and B exist at the same time. The term " / and" in this article describes another type of association object relationship, indicating that there can be two relationships. For example, A / and B can mean: A exists alone, and A and B exist alone. In addition, the character " / " in this article generally indicates that the previous and next associated objects are in an "or" relationship.
[0037] (1) High energy absorption base fabric
[0038] The base fabric can be made of any high-performance fiber, preferably one or more of aramid, high-strength high-modulus polyethylene, and high-strength polyester, and the fineness of the high-performance fiber is 5.5tex-80tex. For example, in some embodiments, 5.5tex, 8.3tex, 11.1tex, 16.7tex, 22.2tex, 44.4tex, and 66.7tex can be selected. The base fabric can be a knitted, woven, braided, or non-woven two-dimensional or three-dimensional fabric. Preferably, a woven fabric is used, whose fabric structure can be plain or twill, preferably 2 / 1 twill, with a warp density of 50-1000 strands / 10cm and a weft density of 50-1000 strands / 10cm. By way of example, in some embodiments, the warp and weft densities can be 50 strands / 10cm, 100 strands / 10cm, 150 strands / 10cm, 200 strands / 10cm, 500 strands / 10cm, 800 strands / 10cm or 1000 strands / 10cm, etc., respectively.
[0039] (II) Polygonal hard protection array
[0040] The hard protective array is evenly arranged in polygons or circles, and the polygons are preferably regular hexagons, sectors, regular pentagons, and triangles; the side length or diameter of the polygonal or circular hard protective array is 0.5-5mm, each array is evenly arranged, and the spacing between adjacent arrays is 0.05-1.5mm. For example, in some embodiments, the side length or diameter is optionally 0.5mm, 1mm, 2mm, 3mm or 5mm, and the spacing between adjacent arrays is optionally 0.05mm, 0.1mm, 1.5mm, etc. If the side length is too small, the bonding force between it and the base fabric will decrease, so it is easy to fall off, and the anti-stab and anti-cut performance will also be greatly reduced and unable to resist external forces. If the side length is too large, the fabric will be too hard and not soft; if the spacing between adjacent arrays is too small, the hardness will also be greater, and the bending flexibility of the fabric will deteriorate; if the spacing is too large, it will not have the desired protective effect, and the probability of being stabbed in the gap will increase.
[0041] (III) Composite materials
[0042] The stab-proof, cut-proof and comfortable breathable composite material of the present invention comprises the above-mentioned high energy absorption base fabric and the above-mentioned polygonal hard protective array attached and fixed to the surface of the above-mentioned high energy absorption base fabric. The composite material can achieve the following levels of indicators such as cut resistance, puncture resistance, waterproofness and wear resistance.
[0043] 1) Anti-cutting performance
[0044] The stab-proof, cut-proof and comfortable breathable composite material prepared by the present invention has a cut-proof performance tested by the ISO13997 method and reaches A7-A9 level of ANSI / ISEA 105-2016 standard.
[0045] 2) Anti-puncture performance
[0046] Using the Couptest cutting tester, under a fixed load, a circular blade is used to cyclically roll and cut the sample back and forth until it is cut. The cotton canvas is used as the reference material for verifying the sharpness of the blade. The reference material and the test sample are cut alternately until five test results are obtained. The cutting resistance is the ratio of the number of cyclic cutting times required to cut the test material to the reference material, that is, the cutting index. The puncture-resistant, cut-resistant, comfortable and breathable composite material prepared by the present invention has a puncture-resistant performance of more than level three according to the EN388-2016 standard.
[0047] 3) Wear resistance
[0048] The puncture-proof, cut-proof, comfortable and breathable composite material prepared by the present invention has a wear resistance of more than level three according to the EN388-2016 standard.
[0049] 4) Waterproof performance
[0050] The stab-proof, cut-proof, comfortable and breathable composite material prepared by the present invention can reach level 4 or above according to GB / T 4745-2012 standard.
[0051] 5) Breathability
[0052] The stab-proof, cut-proof and comfortable breathable composite material prepared by the present invention is based on the GB / T5453-1997 standard and can reach a minimum of 35 mm / s or more.
[0053] The above are the main performance indicators of the stab-proof, cut-proof, comfortable and breathable composite material of the present invention. The product test performance of the specific embodiments is shown in Table 1, and all of them can meet the above requirements of the composite material product.
[0054] (IV) Preparation process of composite materials
[0055] 1) Preparation of high energy absorption base fabric and surface waterproof and oil-proof treatment
[0056] The high energy absorbing base fabric is obtained by using filament or staple yarn made of high-performance fibers such as aramid, high-strength high-modulus polyethylene and / or high-strength polyester, with a warp and weft density of 50-1000 strands / 10cm and a plain or twill weave, preferably a 2 / 1 twill weave.
[0057] The high energy absorption base fabric is surface treated with a waterproof and oil-proof treatment agent, wherein the waterproof and oil-proof treatment agent is a hexafluorocarbon waterproof and oil-proof agent or a fluorine-free waterproof and oil-proof agent, and the ratio of the waterproof and oil-proof agent to deionized water is 20-80:100; the treatment method is: spraying the waterproof and oil-proof treatment agent on the base fabric for 5-20 seconds, drying at 80-120°C, and then baking at 160-180°C for 30-120 seconds to obtain the treated high energy absorption base fabric. In some embodiments, the waterproof and oil-proof treatment agent is a hexafluorocarbon waterproof and oil-proof agent, and specifically, HK GUARD HG-6457, HK GUARD HG-3060, TG-5545, etc. are used. In other embodiments, the waterproof and oil-proof treatment agent can also be a fluorine-free waterproof and oil-proof agent, and specifically, HK GUARD HG-5709, HK GUARDHG-5729, XF-5003, etc. are used.
[0058] The high energy absorption base fabric is treated with a waterproof and oil-proof treatment agent to effectively prevent the flow, diffusion and penetration of the resin preform, thereby preventing the array from being connected into one piece, affecting the forming and making the fabric hard.
[0059] 2) Preparation process of resin preform
[0060] 1) Surface treatment of inorganic powder;
[0061] II) Preparation of curing agent solution: Add latent curing agent powder and accelerator into a container, then add N,N-dimethylformamide, place the mixed container in a 52-60°C water bath and stir continuously until the powder is dissolved and the solution is clear, thereby obtaining a curing agent solution;
[0062] III) Wetting and dispersing the inorganic powder: adding an antioxidant and an anti-settling dispersant to the curing agent solution, and adding the treated inorganic powder, stirring evenly to wet and disperse the inorganic powder;
[0063] IV) Preparation of inorganic powder and resin mixture: The inorganic powder and the thermosetting resin are mechanically stirred to mix evenly, and vacuum is applied to remove excess bubbles to obtain a mixture;
[0064] V) Preparation of resin preform: The mixture is allowed to stand at room temperature for 24-48 hours or at 70-90° C. for 30-60 minutes for pre-curing, and then slowly stirred again to obtain a resin preform.
[0065] In the preparation process of the resin preform,
[0066] The inorganic powder surface treatment method in step 1) is specifically as follows:
[0067] a) Preparation of silane coupling agent treatment agent: prepare silane coupling agent and deionized water in a ratio of 1:15-25 to obtain silane coupling agent treatment agent for standby use; the silane coupling agent is preferably one of KH550, KH560 and KH570;
[0068] b) Surface treatment: Weigh appropriate amounts of silicon dioxide, titanium dioxide, aluminum oxide, wollastonite and barium sulfate, stir evenly, add sufficient amount of silane coupling agent and stir to ensure full contact. The treatment time is 45-120 seconds;
[0069] c) Drying: The inorganic powder treated in the above steps is placed in an oven for drying at a temperature of 80-120°C and a drying time of 30-80 minutes.
[0070] The weight proportions of the raw materials in the above process are: 10-15 parts of silicon dioxide, 16-20 parts of aluminum oxide (corundum), 8-12 parts of wollastonite, 1-5 parts of barium sulfate, 0.5-3 parts of titanium dioxide; 40-60 parts of the thermosetting resin, 7-15 parts of NN-dimethylformamide, 3-6 parts of latent curing agent, 0.1-1.5 parts of accelerator; 5-15 parts of anti-settling dispersant, 0.05-0.2 parts of antioxidant, and 0.1-1.0 parts of silane coupling agent.
[0071] In addition, in a specific feasible embodiment of the present invention, the latent curing agent can be selected from ethylenediamine, hexamethylenediamine, diethylenetriamine, dicyandiamide, diaminodiphenyl sulfone (DDS) or diaminodiphenylmethane (DDM, etc., the accelerator can be selected from DMP-30, EP-184, triethanolamine, 2-methylimidazole, 2-methylimidazole or BDMA, etc., the antioxidant is selected from (3,5-di-tert-butyl-4-hydroxyphenyl) propionate, V72-P, V78-P, V85-P or V76-P, etc., the anti-settling dispersant KYC-918, YRFC-06A, YRFC-01, and the thermosetting resin can be selected from epoxy resin, phenolic resin, urea-formaldehyde resin, unsaturated resin, polyurethane, and one of polyimide.
[0072] 3) Screen printing process
[0073] The mold is placed on top of the high-energy-absorbing base fabric that has been treated with waterproofing and oil repellency, the prepared resin preform is poured into the mold, a scraper is used to apply a certain pressure to the resin preform and move it at a uniform speed, so that the resin preform is squeezed from the mesh part of the mold to the high-energy-absorbing base fabric by the scraper, and then a second curing treatment process is carried out. The curing temperature is 100-130°C and the curing time is 30-60min to form a hard protective array, and then a composite material is obtained; the scraper applies a certain pressure to the resin preform, which can be optionally 0.5-10N. During the curing process, the curing temperature needs to be controlled. If the temperature is too high, the final fabric will become hard and brittle.
[0074] Example 1
[0075] 1) Preparation of high energy absorption base fabric and surface waterproof and oil-proof treatment
[0076] The base fabric is a woven fabric made of aramid filaments with a fineness of 50 tex as raw materials, the fabric structure adopts 2 / 1 twill, the warp density is 200 strands / 10 cm, and the weft density is 200 strands / 10 cm. The base fabric is surface treated with a hexafluorocarbon waterproof and oil-proof agent, and the ratio of the treatment agent to deionized water is 20:100; the treatment method is: spray the waterproof and oil-proof treatment agent on the base fabric for 20 seconds, dry it at 120°C, and then bake it at 150°C for 100 seconds to obtain the treated high energy absorption base fabric.
[0077] The hard protection array is a regular hexagon; the side length is 2 mm, and the distance between adjacent arrays is 1.5 mm.
[0078] 2) Preparation process of resin preform
[0079] I) Inorganic powder surface treatment, the specific process is as follows:
[0080] a) Preparation of silane coupling agent treatment agent: prepare silane coupling agent treatment agent by mixing silane coupling agent and deionized water in a ratio of 1:20 and set aside;
[0081] b) Surface treatment: Weigh appropriate amounts of silicon dioxide, titanium dioxide, aluminum oxide, wollastonite, and barium sulfate, stir evenly, add sufficient amount of silane coupling agent and stir to ensure full contact. The treatment time is 60 seconds;
[0082] c) Drying: Place the treated inorganic powder in an oven for drying at 80°C for 45 minutes.
[0083] II) Preparation of curing agent solution:
[0084] Add latent curing agent powder and accelerator into a container, then add N,N-dimethylformamide, place the mixed container in a 55°C water bath and stir continuously until the powder is dissolved and the solution is clear, thereby obtaining a curing agent solution;
[0085] III) Wetting and dispersing the inorganic powder: adding an antioxidant and an anti-settling dispersant to the curing agent solution, and adding the treated inorganic powder, stirring evenly to wet and disperse the inorganic powder;
[0086] IV) Preparation of inorganic powder and epoxy resin mixture: mechanically stirring the inorganic powder and epoxy resin, mixing them evenly, and vacuuming to remove excess bubbles to obtain a mixture;
[0087] V) Preparation of resin preform: The above mixture is allowed to stand at room temperature for 28 hours or at 80° C. for 45 minutes, and then slowly stirred again to obtain a resin preform.
[0088] The weight proportions of the above raw materials are: 12.9 parts of silicon dioxide, 19.1 parts of aluminum oxide (corundum), 9.8 parts of wollastonite, 2.6 parts of barium sulfate, 1.2 parts of titanium dioxide, 48 parts of the epoxy resin, 10 parts of NN-dimethylformamide, 4.3 parts of latent curing agent, 0.9 parts of accelerator; 8 parts of anti-settling dispersant, 0.1 parts of antioxidant, and 0.3 parts of silane coupling agent.
[0089] 3) Screen printing process
[0090] Place the mold on top of the high energy absorption base fabric, pour the resin preform into the mold, use a scraper to apply a pressure of 0.5-10N to the resin preform and move it at a constant speed, so that the resin preform is squeezed from the mesh part of the mold to the base fabric by the scraper, and then a second curing process is carried out. The curing temperature is 110℃ and the curing time is 45min, thereby obtaining a puncture-proof, cut-resistant, comfortable and breathable composite material. The product display can be found in Figure 1 shown.
[0091] Example 2
[0092] 1) Preparation of high energy absorption base fabric and surface waterproof and oil-proof treatment
[0093] The base fabric is a woven fabric made of high-strength polyester filaments with a fineness of 60tex as raw materials. The fabric structure adopts a plain weave structure, the warp density is 150 strands / 10cm, and the weft density is 150 strands / 10cm. The base fabric is surface treated with a hexafluorocarbon waterproof and oil-proof agent, and the ratio of the treatment agent to deionized water is 40:100; the treatment method is: spray the waterproof and oil-proof treatment agent on the base fabric for 15s, dry it at 130℃, and then bake it at 170℃ for 80s to obtain the treated high-energy absorption base fabric.
[0094] The hard protection array is a regular hexagon; the side length is 1 mm, and the distance between adjacent arrays is 0.5 mm.
[0095] 2) Preparation process of resin preform
[0096] I) Inorganic powder surface treatment, the specific process is as follows:
[0097] a) Preparation of silane coupling agent treatment agent: prepare silane coupling agent treatment agent by mixing silane coupling agent and deionized water in a ratio of 1:18 and set aside;
[0098] b) Surface treatment: Weigh appropriate amounts of silicon dioxide, titanium dioxide, aluminum oxide, wollastonite, and barium sulfate, stir evenly, add sufficient amount of silane coupling agent and stir to ensure full contact. The treatment time is 80 seconds;
[0099] c) Drying: The treated inorganic powder is placed in an oven for drying at a temperature of 90°C and a drying time of 40 minutes.
[0100] II) Preparation of curing agent solution:
[0101] Add latent curing agent powder and accelerator into a container, then add N,N-dimethylformamide, place the mixed container in a 60°C water bath and stir continuously until the powder is dissolved and the solution is clear, thereby obtaining a curing agent solution;
[0102] III) Wetting and dispersing the inorganic powder: adding an antioxidant and an anti-settling dispersant to the curing agent solution, and adding the treated inorganic powder, stirring evenly to wet and disperse the inorganic powder;
[0103] IV) Preparation of inorganic powder and epoxy resin mixture: mechanically stirring the inorganic powder and epoxy resin, mixing them evenly, and vacuuming to remove excess bubbles to obtain a mixture;
[0104] V) Preparation of resin preform: The above mixture is allowed to stand at room temperature for 30 hours or at 90° C. for 60 minutes, and then slowly stirred again to obtain a resin preform.
[0105] The weight proportions of the above raw materials are: 13.5 parts of silicon dioxide, 19.5 parts of aluminum oxide (corundum), 10 parts of wollastonite, 3 parts of barium sulfate, 2 parts of titanium dioxide, 55 parts of the epoxy resin, 12 parts of NN-dimethylformamide, 5 parts of latent curing agent, 1.2 parts of accelerator; 10 parts of anti-settling dispersant, 0.15 parts of antioxidant, and 0.5 parts of silane coupling agent.
[0106] 3) Screen printing process
[0107] Place the mold on top of the high energy absorption base fabric, pour the resin preform into the mold, use a scraper to apply a pressure of 0.5-10N to the resin preform and move it at a constant speed, so that the resin preform is squeezed from the mesh part of the mold to the base fabric by the scraper, and then a second curing process is carried out, the curing temperature is 120℃, and the curing time is 50min, thereby obtaining a puncture-proof, cut-resistant, comfortable and breathable composite material. The product display can be found in Figure 2 shown.
[0108] Example 3
[0109] 1) Preparation of high energy absorption base fabric and surface waterproof and oil-proof treatment
[0110] The base fabric is a woven fabric made of high-strength and high-modulus polyethylene staple yarn with a fineness of 5.5 tex as raw material. The fabric structure adopts plain weave, the warp density is 1000 strands / 10 cm, and the weft density is 1000 strands / 10 cm. The base fabric is surface treated with a fluorine-free waterproof and oil-proof agent, and the ratio of the treatment agent to deionized water is 60:100; the treatment method is: spray the waterproof and oil-proof treatment agent on the base fabric for 10 seconds, dry it at 100°C, and then bake it at 160°C for 60 seconds to obtain the treated high-energy absorption base fabric.
[0111] The hard protection array is circular; the diameter is 3mm, and the spacing between adjacent arrays is 1.2mm.
[0112] 2) Preparation process of resin preform
[0113] I) Inorganic powder surface treatment, the specific process is as follows:
[0114] a) Preparation of silane coupling agent treatment agent: prepare silane coupling agent treatment agent by mixing silane coupling agent and deionized water in a ratio of 1:25 and set aside;
[0115] b) Surface treatment: Weigh appropriate amounts of silicon dioxide, titanium dioxide, aluminum oxide, wollastonite, and barium sulfate, stir evenly, add sufficient amount of silane coupling agent and stir to ensure full contact. The treatment time is 45 seconds;
[0116] c) Drying: The treated inorganic powder is placed in an oven for drying at a temperature of 80°C and a drying time of 80 minutes.
[0117] II) Preparation of curing agent solution:
[0118] Add latent curing agent powder and accelerator into a container, then add N,N-dimethylformamide, place the mixed container in a 52°C water bath and stir continuously until the powder is dissolved and the solution is clear, thereby obtaining a curing agent solution;
[0119] III) Wetting and dispersing the inorganic powder: adding an antioxidant and an anti-settling dispersant to the curing agent solution, and adding the treated inorganic powder, stirring evenly to wet and disperse the inorganic powder;
[0120] IV) Preparation of inorganic powder and epoxy resin mixture: mechanically stirring the inorganic powder and epoxy resin, mixing them evenly, and vacuuming to remove excess bubbles to obtain a mixture;
[0121] V) Preparation of resin preform: The above mixture is allowed to stand at room temperature for 24 hours or at 70° C. for 30 minutes, and then slowly stirred again to obtain a resin preform.
[0122] The weight proportions of the above raw materials are as follows: 10 parts of silicon dioxide, 16 parts of aluminum oxide (corundum), 8 parts of wollastonite, 1 part of barium sulfate, 0.5 parts of titanium dioxide; 40 parts of the epoxy resin, 7 parts of NN-dimethylformamide, 3 parts of latent curing agent, 0.1 parts of accelerator; 5 parts of anti-settling dispersant, 0.05 parts of antioxidant, and 0.1 parts of silane coupling agent.
[0123] 3) Screen printing process
[0124] Place the mold above the high-energy-absorbing base fabric, pour the resin preform into the mold, use a scraper to apply a pressure of 0.5-10N to the resin preform and move it at a uniform speed, so that the resin preform is squeezed from the mesh part of the mold to the base fabric by the scraper, and then a second curing treatment process is carried out with a curing temperature of 130°C and a curing time of 30 minutes, thereby obtaining a puncture-resistant, cut-resistant, comfortable and breathable composite material.
[0125] Example 4
[0126] The base fabric raw material used is high-strength and high-modulus polyethylene staple yarn with a fineness of 5.5 tex, the base fabric fabric structure is 2 / 1 twill, the warp density is 1000 strands / 10 cm, the weft density is 1000 strands / 10 cm, the hard protective array is a regular hexagon with a side length of 5 mm, and the spacing between adjacent arrays is 1.5 mm; the rest is the same as Example 1.
[0127] Example 5
[0128] The hard protection array is a regular hexagon; the side length is 0.5 mm, and the distance between adjacent arrays is 0.05 mm; the rest is the same as in Example 2.
[0129] Example 6
[0130] The base fabric raw material used is aramid filament with a fineness of 80 tex, the base fabric fabric structure is 2 / 1 twill, the warp density is 50 strands / 10 cm, the weft density is 50 strands / 10 cm, the ratio of treatment agent: deionized water = 30:100; the treatment method is: spraying the waterproof and oil-proof treatment agent on the base fabric for 5s, the hard protective array is a regular hexagon; the side length is 0.5 mm, and the distance between adjacent arrays is 0.15 mm; the rest is the same as Example 1.
[0131] Example 7
[0132] The hard protection array is an equilateral triangle; the side length is 0.5 mm, and the distance between adjacent arrays is 0.05 mm; the rest is the same as in Example 2.
[0133] Example 8
[0134] The weight proportions of the raw materials are as follows: 15 parts of silicon dioxide, 20 parts of aluminum oxide (corundum), 12 parts of wollastonite, 5 parts of barium sulfate, 3 parts of titanium dioxide; 60 parts of the epoxy resin, 15 parts of NN-dimethylformamide, 6 parts of latent curing agent, 1.5 parts of accelerator; 15 parts of anti-settling dispersant, 0.2 parts of antioxidant, and 1.0 parts of silane coupling agent.
[0135] The rest is the same as in Example 1.
[0136] Comparative Example 1
[0137] The base fabric is a woven fabric made of aramid filaments as raw materials, with a fineness of 50tex, a fabric structure of 2 / 1 twill, a warp density of 200 strands / 10cm, and a weft density of 200 strands / 10cm. The base fabric is surface treated with a hexafluorocarbon waterproof and oil-proof treatment agent, and the ratio of the treatment agent to deionized water is 20:100; the treatment method is: spray the waterproof and oil-proof treatment agent on the base fabric for 20 seconds, dry it at 120°C, and then bake it at 150°C for 100 seconds to obtain the treated high energy absorption base fabric.
[0138] Comparative Example 2
[0139] The base fabric in Comparative Example 1 is subjected to a pressure of 0.5-10N on the epoxy resin preform using a scraper and moved at a constant speed, so that the resin preform is coated on the base fabric, and then a curing process is performed with a curing temperature of 100°C and a curing time of 60 minutes to obtain a composite material.
[0140] Comparative Example 3
[0141] The inorganic powder and epoxy resin are mechanically stirred and mixed evenly, and the excess bubbles are removed by vacuum to obtain an epoxy resin preform; then, a scraper is used to apply a certain pressure to the epoxy resin preform and move it at a uniform speed, so that the resin preform is coated on the base cloth in Comparative Example 1, and then a curing treatment process is performed, the curing temperature is 100°C, and the curing time is 60 minutes, thereby obtaining a composite material.
[0142] Comparative Example 4
[0143] The base fabric is a woven fabric made of high-strength and high-modulus polyethylene staple yarn with a fineness of 5.5 tex as raw material, with a fineness of 5.5 tex, a fabric structure of 2 / 1 twill, a warp density of 1000 strands / 10 cm, and a weft density of 1000 strands / 10 cm. The inorganic powder and epoxy resin are mechanically stirred and mixed evenly, and the excess bubbles are removed by vacuum to obtain an epoxy resin preform; a scraper is used to apply a certain pressure to the epoxy resin preform and move at a constant speed, so that the resin preform is coated on the base fabric, and then a curing treatment process is performed, the curing temperature is 100°C, and the curing time is 60 minutes, thereby obtaining a composite material.
[0144] The test results of the composite materials or high energy absorption base fabrics prepared in the above-mentioned Examples 1-8 and Comparative Examples 1-4 of the present invention for indicators such as anti-cutting, anti-puncture, waterproofness, air permeability, wear resistance, and abrasion resistance are shown in the following table.
[0145] Table 1 Performance test results of the composite materials of the embodiments of the present invention and the comparative examples
[0146]
[0147] The above description is only an enumeration of preferred embodiments or embodiments of the present invention and is not intended to limit the present invention. For those skilled in the art, the composite material and its preparation process in the present invention are not limited thereto. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A composite material that is puncture-proof, cut-proof, comfortable and breathable, characterized in that: The composite material comprises a hard protective array formed by a high energy absorption base fabric and a circular or polygonal resin preform, wherein the hard protective array is formed by compounding the resin preform on the high energy absorption base fabric by a screen printing method, wherein the high energy absorption base fabric is made of high performance fibers, the high energy absorption base fabric is treated with waterproof and oil proofing, the high performance fibers are filaments or staple fibers, and the high performance fibers are selected from one or more of aramid, high strength and high modulus polyethylene, and high strength polyester, and the fineness of the high performance fibers is 5.5 tex-80 tex; The resin preform is prepared by the following method: S21, surface treatment of inorganic powder; S22, preparation of curing agent solution: add latent curing agent powder and accelerator into a container, then add N,N-dimethylformamide, place the container containing the three mixtures in a 52-60°C water bath and stir continuously until the powder is dissolved and the solution is clear, thereby obtaining a curing agent solution; S23, wetting and dispersing inorganic powder: adding an antioxidant and an anti-settling dispersant to the curing agent solution, and adding the surface-treated inorganic powder, and stirring evenly to wet and disperse the inorganic powder; S24, preparing an inorganic powder-doped resin mixture: mechanically stirring the wetted and dispersed inorganic powder and the thermosetting resin to mix them evenly, and vacuuming to remove excess bubbles to obtain a mixture; S25, preparing a resin preform; after pre-curing the mixture at room temperature for 24-48 hours or at 70-90° C. for 30-60 minutes, slowly stirring again to obtain a resin preform; The composite material has a cut resistance of A7-A9 according to ANSI / ISEA 105-2016 standard, a puncture resistance of above level 3 according to EN388-2016 standard, a waterproof performance of above level 4 according to GB / T 4745-2012, and a wear resistance of above level 3 according to EN388-2016.
2. The composite material according to claim 1, characterized in that: The fabric structure of the high energy absorption base fabric is plain or twill; the warp density of the high energy absorption base fabric is 50-1000 strands / 10cm, and the weft density is 50-1000 strands / 10cm.
3. The composite material according to claim 2, characterized in that: The fabric structure of the high energy absorption base fabric is 2 / 1 twill.
4. The composite material according to claim 1, characterized in that: The high energy absorption base fabric is surface treated with a waterproof and oil-proof treatment agent, wherein the waterproof and oil-proof treatment agent is a hexafluorocarbon waterproof and oil-proof agent or a fluorine-free waterproof and oil-proof agent; the ratio of the waterproof and oil-proof treatment agent to deionized water is 20-60:100; the treatment method is: the high energy absorption base fabric is immersed in the spray treatment agent for 5-20 seconds, then taken out, dried at 80-120°C, and then shaped and baked at 160°C-180°C for 30-120s.
5. The composite material according to claim 1, characterized in that : The inorganic powder includes silicon dioxide, titanium dioxide, aluminum oxide, wollastonite and barium sulfate; the polygon is a regular hexagon, a fan, a regular pentagon, or a triangle; the side length or diameter of the circle or polygon is 0.5-5 mm, each array is evenly arranged, and the distance between adjacent arrays is 0.05-1.5 mm.
6. The method for preparing the composite material according to any one of claims 1 to 5, characterized in that: It includes the following steps: S1. Preparation of high energy absorption base fabric and surface waterproof and oil-proof treatment: S11. The high energy absorbing base fabric has a warp and weft density of 50-1000 roots / 10cm, and the fabric is plain or twill machine-made; S12: the surface is treated with a fluorinated water- and oil-proof agent or a fluorine-free water- and oil-proof agent, the ratio of the fluorinated water- and oil-proof agent or the fluorine-free water- and oil-proof agent to deionized water is 20-60:100; S2, preparing a resin preform; S3. The resin preform is compounded on a high energy absorption base fabric by screen printing to form a hard protective array, thereby obtaining a composite material.
7. The preparation method according to claim 6, characterized in that: In step S3, the screen printing method is specifically as follows: placing the mold on top of the high-energy-absorbing base cloth treated in step S1, pouring a resin preform into the mold, and using a scraper to apply a certain pressure to the resin preform and move it at a uniform speed, so that the resin preform is squeezed from the mesh part of the mold to the high-energy-absorbing base cloth by the scraper, and then performing a curing treatment process, the curing temperature is 100-130°C, and the curing time is 30-60min.
8. The preparation method according to claim 6, characterized in that: In step S21, the inorganic powder surface treatment method is specifically: S211, silane coupling agent treatment agent preparation: silane coupling agent and deionized water are prepared in a ratio of 1:15-25 to obtain a silane coupling agent treatment agent for standby use; S212, surface treatment: weigh appropriate amounts of silicon dioxide, titanium dioxide, aluminum oxide, wollastonite and barium sulfate, stir them evenly, add a sufficient amount of the silane coupling agent treatment agent and stir to ensure full contact, the treatment time is 45-120 seconds; S213, drying: the inorganic powder treated in step S212 is placed in an oven for drying at a temperature of 80-120°C and a drying time of 30-80 minutes.
9. The preparation method according to claim 8, characterized in that: The silane coupling agent is one of KH550, KH560 or KH570.
10. The preparation method according to claim 8, characterized in that: The weight proportions of the above raw materials are: 10-15 parts of silicon dioxide, 16-20 parts of aluminum oxide, 8-12 parts of wollastonite, 1-5 parts of barium sulfate, 0.5-3 parts of titanium dioxide; 40-60 parts of the thermosetting resin, 7-15 parts of NN-dimethylformamide, 3-6 parts of latent curing agent, 0.1-1.5 parts of accelerator; 5-15 parts of anti-settling dispersant, 0.05-0.2 parts of antioxidant, and 0.1-1.0 parts of silane coupling agent.
Citation Information
Patent Citations
High-performance non-metal puncture-proof sheet
CN105696357A
Multifunctional ventilating type protection material and preparation method thereof
CN101181661A
Stab-resistant material and manufacturing method thereof
CN101922893A
Resin-formed flexible puncture-proof fabric and preparation method thereof
CN103184695A
Bonding forming method of flexible stab-preventing material and stab-preventing body
CN103791778A